Vitamin B12 Deficiency and Psychiatric Manifestations-A Consise Review - Roshan Kumar Jha; Deepika Kanyal; Ritu Devi; Lata Kanyal Butola (Indian Journal of Forensic Medicine & Toxicology, 2021)
Vitamin B12 deficiency may contribute to the pathogenesis of neuropsychiatric disorders such as mental confusion, memory changes, cognitive slowing, mood disorder, violent behaviour, fatigue, delirium and paranoid psychosis. Vitamin B12 plays a crucial role in cell reproduction, normal erythropoiesis, nucleoprotein and myelin synthesis, normal growth, DNA synthesis, and one carbon metabolism. Vitamin B12 helps in synthesis of methionine from homocysteine and conversion of methylmalonylcoA to succinylcoA. Methionine is converted to SAM which donates its methyl group to myelin, membrane phospholipids and various neurotransmitters and free THF is liberated from N5 methyl THF which is used in synthesis of purine, pyrimidine and nucleic acid. An elevated level of Hcy as a neurotoxin was also shown to affect the redox signalling pathways in neurons through the generation of reactive oxygen species (ROS) and a decrease in endogenous antioxidants. If patterns of DNA methylation in redox-related genes can modulate cognitive impairment caused by vitamin B12 deficiency and hyperhomocysteinaemia is therefore of interest, low levels of vitamin B12 can cause serious cognitive dysfunction. Psychiatric symptoms attributable to vitamin B12 deficiency have been described for decades. The earlier studies are for the most part in accord with more recent ones, despite being diagnostically less precise in psychological and hematologic terms. These symptoms tend to fall into many clinically distinct categories: slow cerebration; confusion; memory changes; delirium, with or without hallucinations and/or delusions; depression; acute psychotic states; and more rarely) reversible manic and schizophreniform states. In conclusion, psychiatric disorders can be rare manifestations of vitamin B12 deficiency, which are reversible with therapy. Serum Vitamin B12 level should be checked in patients with psychiatric manifestations as it results in neuro psychiatric manifestations such as peripheral neuropathy, myeloneuropathy, cerebellar ataxia, optic atrophy, delirium, dementia, psychosis and mood disorders